2017
DOI: 10.1007/s13760-017-0755-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprognostication after adult cardiac arrest treated with targeted temperature management: task force for Belgian recommendations

Abstract: The prognosis of patients who are admitted to the hospital after cardiac arrest often relies on neurological examination, which could be significantly influenced by the use of sedative drugs or the implementation of targeted temperature management. The need for early and accurate prognostication is crucial as up to 15-20% of patients could be considered as having a poor outcome and may undergo withdrawal of life-sustaining therapies while a complete neurological recovery is still possible. As current practice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 86 publications
1
32
0
Order By: Relevance
“…When evaluating the cortical responses of both hemispheres, the SEP amplitude was defined as the highest amplitude of N20/P25, as indicated by Endisch et al 14 The outcome was dichotomized between recovery of consciousness (GOS score [3][4][5] and no recovery of consciousness (GOS score 1-2). The mean values for SEP amplitude for different outcome groups and different EEG patterns were analysed by ANOVA followed by post-hoc analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…When evaluating the cortical responses of both hemispheres, the SEP amplitude was defined as the highest amplitude of N20/P25, as indicated by Endisch et al 14 The outcome was dichotomized between recovery of consciousness (GOS score [3][4][5] and no recovery of consciousness (GOS score 1-2). The mean values for SEP amplitude for different outcome groups and different EEG patterns were analysed by ANOVA followed by post-hoc analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent papers have reported that EEG markers can predict outcomes with relatively high specificity and sensitivity, 6 and that a multimodal approach incorporating more tools must always include EEG. 5 However, only a few papers have analysed the association between SEP and EEG in CA patients for prognostic purposes, 23 …”
Section: Recent Recommendations From the European Resuscitationmentioning
confidence: 99%
See 2 more Smart Citations
“…In the setting of hypothermia, the variables used for neurologic prognostication have unacceptably high false-positive rates. 6,7 More recent guidelines suggest delaying prognostic assessments when TTM is used 4,8 ; however, time to awakening in HIBI varies and up to 1 in 7 patients may experience a delayed awakening with favorable neurologic outcome. 9 DISCUSSION Given the complex relationship between TTM and neurologic prognosis, it is important to reevaluate previously ascribed indicators of poor prognosis.…”
Section: Sectionmentioning
confidence: 99%